Radiation damage and thermal annealing in tunnel structured hollandite materials. (March 2021) - Zhao, Mingyang; O'Quinn, Eric; Birkner, Nancy; Xu, Yun; Lang, Maik; Brinkman, Kyle
Abstract: Three tunnel structured hollandite samples (Cs1.33 Ga1.33 Ti6.67 O16, Cs1.33 Fe1.33 Ti6.67 O16, and Cs1.33 Zn0.67 Ti7.33 O16 ) with demonstrated thermodynamic stability and chemical durability were synthesized and irradiated by a 1.1 GeV Au ion beam in order to study effects of B-site dopants on radiation stability. A crystalline-to-amorphous transformation induced by the high-energy ion irradiation was confirmed by complementary characterization techniques sensitive to different length-scales, such as powder X-ray diffraction, Raman spectroscopy and neutron total scattering. High-temperature oxide melt solution calorimetry was performed to determine the energy landscape before and after ion irradiation. Together, structural and thermodynamic analyses demonstrated distinctly different radiation responses of the hollandite with different B-site dopants; the Ga-substituted hollandite exhibited the smallest enthalpy of damage indicating the best radiation stability among the three samples. The hypothesized origin of the different radiation responses is the structural feature in the binary oxide form of the respective B-site dopants (e.g., Ga2 O3 versus Fe2 O3 /ZnO for Ga and Fe/Zn dopants, respectively). Moreover, thermal analysis (i.e., differential scanning calorimetry) was conducted to investigate structural changes from the irradiation induced damaged states after thermal annealing. Results of thermal analysis revealed that the annealing-induced structural evolution of the radiation damaged hollandite structure is complex and decoupled at different length-scales. The long-range periodic structure (nanometers) was not recovered after thermal annealing and structural changes over a shorter range (≤ ∼3 Å) occurred in multiple steps during the annealing process. Graphical abstracts: Image, graphical abstract